2012
DOI: 10.3748/wjg.v18.i40.5734
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for recurrence of gastrointestinal bleeding due to Dieulafoy's lesion

Abstract: Endoscopic treatment of DL is safe and effective. Adrenaline monotherapy and arterial (spurting) bleeding are associated with a high rate of bleeding recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 37 publications
5
35
2
3
Order By: Relevance
“…Jamanca-Poma et al reported that, despite the high rate of comorbidities, no significant relationship was found between comorbidity and re-bleeding risk in Dieulafoy patients [40]. In the study of Park and colab, kidney disease and infection were significant predictors of re-bleeding in patients with DL, especially when the combination of infection and kidney disease was not properly controlled by medical treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Jamanca-Poma et al reported that, despite the high rate of comorbidities, no significant relationship was found between comorbidity and re-bleeding risk in Dieulafoy patients [40]. In the study of Park and colab, kidney disease and infection were significant predictors of re-bleeding in patients with DL, especially when the combination of infection and kidney disease was not properly controlled by medical treatment.…”
Section: Discussionmentioning
confidence: 94%
“…DL is most commonly found in the lesser curvature of the stomach, with up to 95 % of stomach lesions located within 6 cm of the gastroesophageal junction [1,2,[6][7][8], where the stomach gets its blood supply from branches of the left and right gastric artery instead of the submucosal plexus [6,9]. Besides the stomach, DL has also been described in other locations, including the duodenum, colon, esophagus, jejunum, ileum, rectum, and bronchus [7,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The usual clinical picture is painless, massive and recurrent gastrointestinal bleeding [2,4]. It occurs most commonly in the stomach (75%), in the small curvature (up to 6 cm from the gastroesophageal junction in 80% to 95% of cases) [1,2]. The diagnosis is made by endoscopy, sometimes difficult, due to the size of the lesion, normal aspect of the adjacent mucosa and intermittent bleeding, requiring multiple procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with non-steroidal anti-inflammatory drugs, aspirin and antiplatelet use [4]. The usual clinical picture is painless, massive and recurrent gastrointestinal bleeding [2,4]. It occurs most commonly in the stomach (75%), in the small curvature (up to 6 cm from the gastroesophageal junction in 80% to 95% of cases) [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation